Living opposite to the hospital of St John excavations in medieval Northampton, 2014 - Brown, Jim W. (Archaeopress Publishing, 2021)
Living Opposite to the Hospital of St John: Excavations in Medieval Northampton 2014 presents the results of archaeological investigations undertaken on the site of new county council offices being built between St. John's street and Angel Street, Northampton in 2014. The location was of interest as it lay directly opposite the former medieval hospital of St. John, which influenced the development of this area of the town.0Initially open ground situated outside the Late Saxon burh, the area was extensively quarried for ironstone during the earlier part of the 12th century, and by the mid-12th century, a few dispersed buildings began to appear. Domestic pits and a bread oven were located to the rear of Angel Street along with a carver's workshop, which, amongst other goods, produced high-quality antler chess pieces. This workshop is currently without known parallel. The timber workshop was refurbished once and then replaced in stone by the mid-13th century.
Keywords: Geschichte 1100-1550; Ausgrabung; Funde; Northampton; Hospital of St. John (Northampton, England); Excavations (Archaeology) / England / Northampton; Northampton (England) / Antiquities; Excavations (Archaeology); England / Northampton